The serum levels of gasdermin D in uremic patients and its relationship with the prognosis: a prospective observational cohort study - XiaPing Zhang; Bo Yang (Renal Failure)
Objective This study aimed to explore the serum levels of gasdermin D (GSDMD) in uremic (end-stage kidney disease, ESKD) patients and their correlation with vascular calcification (VC) and clinical results.Methods This prospective observational cohort study enrolled 213 ESKD patients who were undergoing regular maintenance hemodialysis (MHD) for > 3 months in our hospital from August 2019 to July 2022. The abdominal aortic calcification score (AACS) was used to assess the VC condition of patients with ESKD. Serum GSDMD, caspase-1, interleukin (IL)-6, IL-1β, IL-18 and C-reactive protein (CRP) levels were measured using enzyme-linked immunosorbent assay (ELISA). Demographic and clinical data were obtained. All patients were followed up for 1 year, and patients with major adverse cardiovascular events (MACE) were defined as having a poor prognosis. All data used SPSS 26.0 to statistical analyses.Results The serum total cholesterol (TC) levels of patients in the AACS > 4 group were significantly elevated compared with those in the AACS ≤ 4 group. In addition, ESKD patients with an AACS > 4 had significantly higher serum levels of GSDMD, caspase-1, IL-6, IL-18 and IL-1β. Moreover, Pearson’s analysis supported a positive correlation between GSDMD and caspase-1, IL-6, and IL-1β. In addition, we found that GSDMD levels were positively correlated with the clinical data (AACS scores and serum TC levels) of patients with ERSD. Additionally, ROC curves showed that the serum levels of GSDMD could be a potential predictive biomarker of moderate/severe VC and prognosis in patients with ESKD. Finally, the results of logistic regression indicated that GSDMD and AACS scores were risk factors for poor prognosis in patients with ESKD.Conclusion Serum GSDMD levels were remarkably elevated in patients with ESKD with moderate/severe calcification. In addition, serum levels of GSDMD could be a potential predictive biomarker of moderate/severe VC and prognosis in patients with ESKD.